Multiple two-polymerase mechanisms in mammalian translesion DNA synthesis - Livneh, Zvi; Z, Omer; Shachar, Sigal (Cell cycle (Georgetown, Tex.), 2010)
The encounter of replication forks with DNA lesions may lead to fork arrest and/or the formation of single-stranded gaps. A major strategy to cope with these replication irregularities is translesion DNA replication (TLS), in which specialized error-prone DNA polymerases bypass the blocking lesions. Recent studies suggest that TLS across a particular DNA lesion may involve as many as four different TLS polymerases, acting in two-polymerase reactions in which insertion by a particular polymerase is followed by extension by another polymerase. Insertion determines the accuracy and mutagenic specificity of the TLS reaction, and is carried out by one of several polymerases such as polη, polκ or polι. In contrast, extension is carried out primarily by polζ. In cells from XPV patients, which are deficient in TLS across cyclobutane pyrimidine dimers (CPD) due to a deficiency in polη, TLS is carried out by at least two backup reactions each involving two polymerases: One reaction involves polκ and polζ, and the other polι and polζ. These mechanisms may also assist polη in normal cells under an excessive amount of UV lesions.